Analysis of Organizational Governance and Strengthening Strategies for MSME Sustainability: A Case Study of the Geothermal Coffee Process, a Fostered Partner of PT Pertamina Geothermal Energy in the Kamojang Area - Muhammad Fawaz Aldisar; Katiya Nahda (SENTRALISASI, 2026)
This study aims to analyze organizational governance, identify challenges, and formulate governance strengthening strategies to support the sustainability of Geothermal Coffee Process (GCP), a CSR-based MSME fostered by PT Pertamina Geothermal Energy Area Kamojang. A qualitative case study approach was employed using interviews, observations, and documentation. The findings reveal that CSR support has contributed to business development through production facilities, training, mentoring, and promotion. However, GCP still faces governance challenges, including informal organizational structures, limited managerial capacity, inadequate administrative and financial systems, limited marketing activities, and the absence of legal status. The study recommends strengthening organizational legality, managerial capabilities, administrative systems, and marketing strategies to improve competitiveness and ensure long-term business sustainability.